1994
DOI: 10.3109/08916939409010651
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterisation of TPO Autoantibodies Using Combinatorial Phage Display Libraries

Abstract: Thyroid lymphocyte RNA from a Hashimoto patient with high serum levels of autoantibodies to thyroid peroxidase (TPO) was used to construct a phage display antibody library in the phagemid vector pComb3. The library (100,000cfu) encoded IgG1 heavy chains together with kappa light chains. Selection of the phages displaying TPO antibody on TPO-coated ELISA plates yielded a phage population enriched for surface expression of TPO antibody Fabs. 3 different Fabs specific for TPO were subsequently isolated with affin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
3

Year Published

1995
1995
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 48 publications
3
23
0
3
Order By: Relevance
“…However, these same primers have been used extensively to successfully recover highly diverse collections of mAbs from human donors. Moreover, these recombinant antibody panels have been shown to reproduce many of the characteristics of the commensurate in vivo response against both pathogens and autoantigens (29,(33)(34)(35)(36)(37). Comparing the dominant antibody sequences we recovered from the patients with MS to the nearest germ-line V H or V L segment revealed that one of the two dominant heavy chains and both of the dominant light chains were heavily somatically mutated, possessing homologies of 90 to 96% to the closest germ-line gene.…”
Section: Resultsmentioning
confidence: 99%
“…However, these same primers have been used extensively to successfully recover highly diverse collections of mAbs from human donors. Moreover, these recombinant antibody panels have been shown to reproduce many of the characteristics of the commensurate in vivo response against both pathogens and autoantigens (29,(33)(34)(35)(36)(37). Comparing the dominant antibody sequences we recovered from the patients with MS to the nearest germ-line V H or V L segment revealed that one of the two dominant heavy chains and both of the dominant light chains were heavily somatically mutated, possessing homologies of 90 to 96% to the closest germ-line gene.…”
Section: Resultsmentioning
confidence: 99%
“…Several TPO Fabs have been produced using either bacteriophage vector (7,9) or phage display vector pComb3 (10,11,16,35,36). Despite the fact that individual H and L chain genes of the TPO Fab already described are clearly those used in vivo, it has yet to be proved whether separate amplification of heavy and light chains and their random recombination produce the same H and L chains pairing as in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…3), recombinant human Ab fragments have been produced using phage library technology (4 -6). Several groups have used this technology to generate specific human anti-TPO Fabs (7)(8)(9)(10)(11). These Fabs have been widely analyzed in terms of epitope specificity and variable genes usage.…”
mentioning
confidence: 99%
“…Average homology for antibodies derived by cellular methods from 4 anti-HIV-1 gpl20 antibodies was 89% (26) and from two antitetanus toxoid antibodies was 92.5% (27). The average homology for library-derived antibodies from 18 anti-thyroid peroxidase antibodies was 90% (28)(29)(30). In contrast, the average homology to germline of the VH genes from the SLE library in Table 1 ies with the highest affinity for DNA and Crithidia-positive staining were the closest to germline (SI-1, -40 and -32 have homologies of 98%, 99%, and 98%, respectively).…”
Section: Methodsmentioning
confidence: 99%